An Extended Prognostic Index of the ISSWM Score Based on Thyroid Complications in Waldenström Macroglobulinemia/Lymphoplasmacytoid Lymphoma - Hu, Xinting; Wang, Hua; Yuan, Dai; Qu, Huiting; Li, Ying; Wang, Na; Wang, Xianghua; Liu, Xin; Xu, Hongzhi; Zhang, Ya; Wang, Xin (Frontiers in Oncology, 2022)
Waldenström macroglobulinemia/ lymphoplasmacytoid lymphoma (WM/LPL) is a rare lymphoproliferative neoplasm characterized by clonally related lymphocytes, lymphoplasmacytic cells, and plasma cells proliferation. WM/LPL patients commonly presents with elevated immunoglobulin, predominantly immunoglobulin M (IgM). Previous studies reported that thyroid dysfunction was associated with the development and progression in solid tumors. However, only limited information is available on the correlation between thyroid complications and lymphoid malignancies. The aim of our study was to explore the prognostic significance of thyroid complications in WM/LPL. Herein, 13.3% of WM/LPL patients were diagnosed with thyroid complications, which were significantly associated with unfavorable progression free survival (PFS), overall survival (OS), and adverse treatment response. Co-existing thyroid disease was significantly related to alleviated serum IgM level, providing an answer to practical problems. Furthermore, the presence of thyroid complications was identified as an independent prognostic indicator for PFS in WM/LPL. Incorporating the ISSWM score with thyroid complications was superior to ISSWM alone in risk stratification and prognostic prediction. Furthermore, subgroup analyses of WM/LPL patients displayed that subclinical hypothyroidism predicted undesirable outcome at early stage. These results were also supported by independent microarray dataset analyses. In conclusion, the primary strength of this study is that it provides robust real-world evidence on the prognostic role of thyroid complications, highlighting further clinical concern in the management of WM/LPL patients.